PENGARUH SERVICE QUALITY, PERCEIVED VALUE DAN TRUST TERHADAP MERCHANT SATISFACTION DENGAN LAYANAN PEMBAYARAN QRIS PADA SEKTOR UMKM DI JAWA BARAT - Nafila, Tasya; Ariyanti, Maya (eProceedings of Management, 2025)
QRIS as an innovation in digital payment systems, plays an important role in driving financial inclusion andfacilitating fast and secure transactions. Against the backdrop of rapid digital technology development andincreasing digital transactions in Indonesia, this study uses quantitative methods to explore the factors thatinfluence QRIS adoption by users. This study aims to analyze the effect of service quality, perceived value and usertrust on merchant satisfaction with the Quick Response Code Indonesian Standard (QRIS) payment method in theWest Java MSME sector. This study aims to see how service quality, perceived value and user trust affect merchantsatisfaction when using the Quick Response Code Indonesian Standard (QRIS) payment service in the MSMEsector in West Java. The research method used is quantitative with a survey approach, involving 453 respondentswho are MSME players who use QRIS for their business operations. Partial Least Squares Structural EquationModeling (PLS-SEM) was used to analyze the data. The results of this study show that service quality and perceivedvalue from customers have a positive effect on trust, then perceived value from users and trust have a positiveeffect on user satisfaction, but service quality has a negative effect on user satisfaction. Trust also contributesKeywords : Customer Satisfaction, Customer Trust, Perceived Value, Service Quality